Interfacial abruptness in axial Si/SiGe heterostructures in nanowires probed by scanning capacitance microscopy. Issue 2 (28th January 2014) - Periwal, P.; Bassani, F.; Patriarche, G.; Latu‐Romain, L.; Brouzet, V.; Salem, B.; Baron, T.
<x xml:space="preserve">Abstract</x> Si/SiGe heterostructured nanowires (hNWs) were grown by catalyst mediated vapor–liquid–solid mechanism via chemical vapor deposition. As‐grown hNWs were characterized by scanning electron microscopy, transmission electron microscopy, and scanning capacitance microscopy (SCM). All these techniques allow us to spatially delineate Si/SiGe and SiGe/Si heterojunctions and show an asymmetry in terms of abruptness between these two interfaces. Material SCM contrast in Si/Ge system is explained by a difference of native oxide quality.